The eagle's claw [compact disc, unabridged] : a novel of the Battle of Midway - Shaara, Jeff, 1952- (Random House, 2021)
A master of epic military fiction, the New York Times bestselling author of To Wake the Giant makes Midway personal as he takes listeners inside the hearts and minds of the heroes of one of World War II's most pivotal moments. Jeff Shaara recounts in electrifying detail the U.S. Navy's surge to defend its country in what will become known as one of the most definitive and heroic examples of combat ever seen: the Battle of Midway. In this biting new tale, Shaara shares the stories of all ranks and the unique sacrifices each man is compelled to bravely make for the sake of country, freedom, and honor.